2021
DOI: 10.1101/2021.06.02.446729
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Mechanism of Replication Stalling and Recovery within Repetitive DNA

Abstract: Accurate chromosomal DNA replication is essential to maintain genomic stability. Genetic evidence suggests that certain repetitive sequences impair replication, yet the underlying mechanism is poorly defined. Replication could be directly inhibited by the DNA template or indirectly, for example by DNA-bound proteins. Here, we reconstituted replication of mono-, di- and trinucleotide repeats in vitro using eukaryotic replisomes assembled from purified proteins. We found that structure-prone repeats are sufficie… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(25 citation statements)
references
References 95 publications
(129 reference statements)
2
23
0
Order By: Relevance
“…Stalling induced by a single G4-or i-motif-forming sequence was persistent, although relatively weak when compared to other types of structure-prone sequences 45 .…”
Section: Replisome Stalling Is Dependent On the Probability Of Struct...mentioning
confidence: 86%
See 4 more Smart Citations
“…Stalling induced by a single G4-or i-motif-forming sequence was persistent, although relatively weak when compared to other types of structure-prone sequences 45 .…”
Section: Replisome Stalling Is Dependent On the Probability Of Struct...mentioning
confidence: 86%
“…Although Ctf4 is usually excluded from our reactions as it has minimal effect on budding yeast replication 48 , we have included Ctf4 in our experiments with Chl1, so we can infer that the lack of rescue by Chl1 is not due to its inability to be recruited to replication forks. Previous work has shown that Pif1 can rescue forks stalled at poly(dG)n and poly(dC)n sequences 45 . Consistent with this, Pif1 was also able to rescue forks stalled at both G4s and i-motifs (Fig.…”
Section: Stalling At G4s and I-motifs Can Be Rescued By A Specialised...mentioning
confidence: 99%
See 3 more Smart Citations